2023
DOI: 10.3390/pr11061697
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship between the Time Constant Ratio and Plug-Flow Behaviour in the Pneumatic Conveyance of Biomass Material

Abstract: This study introduces a novel methodology to evaluate the behaviour of biomass material by examining the ratio of aeration and deaeration time constants. To this end, a series of tests were conducted on four different materials, namely, cottonseed, wood chips, wood pellets, and wheat straw, in order to investigate their aeration and deaeration behaviours. The study derives the aeration and deaeration pressure drop equations, and discusses the corresponding time constant expression. Subsequently, the four mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Song et al carried out experiments alongside with simulation to study the conveying characteristics of shrimp feed pellets, where they constructed a correlation between system energy consumption and solid-gas ratio [11]. Rajabnia et al investigated the aeration and deaeration behaviours of four different biomass materials and further proposed a new algorithm to reduce trial test, providing a novel approach for predicting flow modes [7]. Alizadeh et al specifically carried out study on perennial ryegras to examine the effects of particle mass, size and moisture content on the performance of pneumatic conveying, with an emphasis on terminal velocity and drag coefficient [51].…”
Section: Perspective Of Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Song et al carried out experiments alongside with simulation to study the conveying characteristics of shrimp feed pellets, where they constructed a correlation between system energy consumption and solid-gas ratio [11]. Rajabnia et al investigated the aeration and deaeration behaviours of four different biomass materials and further proposed a new algorithm to reduce trial test, providing a novel approach for predicting flow modes [7]. Alizadeh et al specifically carried out study on perennial ryegras to examine the effects of particle mass, size and moisture content on the performance of pneumatic conveying, with an emphasis on terminal velocity and drag coefficient [51].…”
Section: Perspective Of Experimentsmentioning
confidence: 99%
“…Halstensen et al reported their design of an on-line monitoring device to acquire the velocity of feed pellet [6]. Rajabnia et al investigated into the relationship between the time constant ratio and plug-flow behavior on differet biomass materials including cottonseed and wood pellet [7]. Apart from the aforementioned experimental works, some other researchers focus on theoretical simulation.…”
mentioning
confidence: 99%